Peak Oxygen Uptake on Cardiopulmonary Exercise Test Is a Predictor for Severe Arrhythmic Events during Three-Year Follow-Up in Patients with Complex Congenital Heart Disease - Felix von Sanden; Svetlana Ptushkina; Julia Hock; Celina Fritz; Jürgen Hörer; Gabriele Hessling; Peter Ewert; Alfred Hager; Cordula M. Wolf (Journal of Cardiovascular Development and Disease, 2022)
Patients with congenital heart disease (CHD) are at increased risk for severe arrhythmia and sudden cardiac death (SCD). Although implantable cardioverter defibrillators (ICD) effectively prevent SCD, risk stratification for primary prophylaxis in patients with CHD remains challenging. Patients with complex CHD undergoing CPET were included in this single-center study. Univariable and backwards stepwise multivariable logistic regression models were used to identify variables associated with the endpoint of severe arrhythmic event during three years of follow-up. Cut-off values were established with receiver operating characteristic (ROC) curve analysis. Survival analysis was conducted via Kaplan–Meier plots. Severe Arrhythmia was documented in 97 of 1194 patients (8.1%/3 years). Independent risk factors for severe arrhythmia during follow-up were old age and a low peak oxygen uptake (<semantics><mover>V.</mover></semantics>O2peak) on multivariable analysis. Patients with more advanced age and with <semantics><mover>V.</mover></semantics>O2peak values of less than 24.9 mL/min/kg were at significantly increased risk for the occurrence of severe arrhythmias during follow-up. The combined analysis of both risk factors yielded an additional benefit for risk assessment. Age at CPET and <semantics><mover>V.</mover></semantics>O2peak predict the risk for severe arrhythmic events and should be considered for risk stratification of SCD in patients with complex CHD.